Voltage balancing control of hybrid MMC under over-modulation situations with optimal circulating current injection. (September 2022) - Zhang, Yaqian; Zhang, Jianzhong; Deng, Fujin; Din, Zakiud
Highlights: The optimal approach of second-order harmonic circulating current (SHCC) injection is proposed to achieve the voltage balancing of hybrid MMC. The characteristics of the critical voltage balancing state are disclosed for the hybrid MMC. The feedback control of the capacitor voltage is put forward to generate the optimal reference of the SHCC. The simulations and experiments are carried out to verify the effectiveness of the proposed approach of optimal SHCC injection. Abstract: The hybrid modular multilevel converter (MMC), applied in high voltage direct current (HVDC) transmission systems, can operate in over-modulation mode to handle the abnormal situations of reduced HVDC voltage due to the extreme atmospheric environment. However, it might suffer from severe voltage imbalance between the half-bridge submodule (HBSM) and full-bridge submodule (FBSM) capacitors when the HVDC voltage is lower than certain limitation. The approach of injecting the second-order harmonic circulating current (SHCC) will be effective to solve this problem. In order to minimize the power losses caused by the SHCC injection, an approach of optimizing the SHCC reference is proposed in this paper to realize the voltage balancing. For the hybrid MMC under the over-modulation situations, the critical states of voltage balancing between the HBSM and FBSM capacitors are derived at the first time. Based on this, the voltage feedback control is put forward to acquire the optimal reference SHCC accurately and flexibly. The effectiveness of the proposed approach of optimal SHCC injection is verified by the simulation and experiment results. Compared with the existing approaches of SHCC injection, it demonstrates that the proposed approach can achieve the lowest power losses with reliable voltage balancing.